The Balanced Learning Management Approaches with Students’ Interesting for Sanya Experimental Primary Schools - Zhiru, Han; Chiwpreecha, Dr.Kesinee (Journal of Dhamma for Life, 2023)
The aims of this research were 1) to study the current states desirable states and priority need index of Balanced Learning Management Approaches with students' interesting of Sanya Experiment Primary Schools, 2) to study the guidelines for Balanced Learning Management Approaches with students' interesting of Sanya Experiment Primary Schools. A mixed method design of quantitative and qualitative analysis is employed. The data were collected from 12 sample schools, choosing one school to represent for informants included school principals, vice-principals and teachers, accounting for 90 people. The research instrument used in the study was asked to complete with the five-point Likert scale. Data were analyzed by using descriptive statistics (mean, standard deviation, frequency, percentage, modified priority need index (PNI Modified), and on the qualitative study.an interview 7 experts from Semi -Structural Interview, the descriptive statistics is used through the statistical content analysis.